2008
DOI: 10.1029/2007jd009700
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lightning activity and ice fluxes in thunderstorms

Abstract: [1] It is generally believed that a strong updraft in the mixed-phase region of thunderstorms is required to produce lightning. This is the region where the noninductive charging process is thought to generate most of the storm electrification. Analytic calculations and model results predict that the total lightning frequency is roughly proportional to the product of the downward mass flux of solid precipitation (graupel) and the upward mass flux of ice crystals. Thus far this flux hypothesis has only been tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
228
4
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(251 citation statements)
references
References 84 publications
16
228
4
3
Order By: Relevance
“…Improved representation of cloud ice in models now allows the implementation of another aspect of the theory, the upward flux of ice crystals. Deierling et al (2008) have shown that the upward ice flux displays a strong linear correlation with lightning flashes in 11 observed US storms.…”
Section: A New Ice-flux-based Parametrisation (Iceflux)mentioning
confidence: 99%
See 2 more Smart Citations
“…Improved representation of cloud ice in models now allows the implementation of another aspect of the theory, the upward flux of ice crystals. Deierling et al (2008) have shown that the upward ice flux displays a strong linear correlation with lightning flashes in 11 observed US storms.…”
Section: A New Ice-flux-based Parametrisation (Iceflux)mentioning
confidence: 99%
“…The result is net accumulation of opposite charge in different parts of the thundercloud. This has been shown to be a realistic theory through a combination of laboratory, field measurement and satellite studies (Williams, 1989;Blyth et al, 2001;Petersen et al, 2005;Saunders, 2008;Deierling et al, 2008;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lightning intensity was closely linked with convection intensity. The strong updraft, a deep ice water mixing region, and large ice particles' flux may enhance lightning activities of a thunderstorm [6][7][8]. The intimate connection between electrical activity and some factors in the mixed-phase region was mainly due to the non-inductive charging process where rebounding collisions between big and small ice particles lead to appreciable charge separation.…”
Section: Introductionmentioning
confidence: 99%
“…Petersen et al (2005) found a linear relationship between total lightning flash rate and ice water path, independent of the regime (land, ocean or coastal zones). Likewise, based on the charging zone concept, several studies have shown strong correlation between the total (intra-cloud and cloudto-ground lightning) flash rate and the precipitable and nonprecipitable ice masses (Blyth et al, 2001;Latham et al, 2004Latham et al, , 2007Deierling et al, 2008). The terms precipitable and non-precipitable ice masses are associated with the hydrometeor types likely to precipitate or not, relative to the convective core updraft, i.e., denser particles like hail and graupel can precipitate over the convective core and are defined as precipitable ice mass, while snowflakes and ice crystals cannot and are therefore defined as non-precipitable ice mass.…”
Section: Cloud Electrification: Total Flash Estimated From Ice Mass Fmentioning
confidence: 99%